Cation exchange in a 3D perovskite-synthesis of Ni(0.5)TaO₃. - Amano Patino, M; Smith, T; Zhang, W; Halasyamani, P; Hayward, M (American Chemical Society, 2014)
Reaction of NiCl2 with NaTaO3 leads the formation of the perovskite phase Ni(0.5)TaO3, via a topochemical nickel-for-sodium cation exchange in which the framework of apex-linked TaO6 octahedra present in the parent phase is retained. Neutron powder diffraction data indicate Ni(0.5)TaO3 adopts a structure analogous to the paraelectric phase of LiTaO3, with triclinic P1 crystallographic symmetry. Although Ni(0.5)TaO3 has features which make it a good candidate phase for magnetoelectric multiferroic behavior, the phase remains paramagnetic in the temperature range 15 < T (K) < 300, and detailed crystallographic characterization and analysis of SHG activity indicate it retains a centrosymmetric structure down to the lowest temperatures measured (5 K). Topochemical cation exchange reactions of 3D perovskite oxides offer the opportunity to prepare a wide range of novel metastable phases in a rational manner with a high degree of synthetic control.